Organic Products –Manufacturing and Marketing Companies in India - Priyadarshini, Marka; Ramanjaneyulu, A. V.; Chaitanya, T.; Kumar, G. Santosh; Yakadri, M. (Chronicle of Bioresource Management, 2023)
Green and White revolution technologies in India have led the country to achieve self-sufficiency in food and dairy products production. But, excessive use of chemicals resulted in chemical residues in food products, degradation of natural resource base, environmental pollution and health hazards. The A1 milk from exogenous animals is unhealthy for human beings. Further, inorganic clothing and personal care items are exhibiting long term ill effects on human health and ecosystem. This led to increased demand for organic products now a days and mushrooming of such companies. In this article, an attempt was made to compile and enlist the information on some of the major organic products and producing companies in India and the need for scientific validation of products produced through organic and natural farming.